Islamic Education Leadership Controversy: Contesting the Effectiveness of Traditional Approaches in Facing the Digital Era - Afif, Muhammad (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2024)
This research aims to conduct an in-depth analysis of the controversy that has arisen regarding the effectiveness of traditional approaches in Islamic educational leadership in the digital era and to find updates or new innovations in leadership strategies that can overcome the challenges of the digital era. In this research, a qualitative case study approach is used to explore and analyze leadership controversies in Islamic education, especially related to the effectiveness of traditional approaches in facing the digital era. Data analysis was carried out using an interpretive paradigm with source and method triangulation techniques to ensure the validity of the data. Thematic analysis techniques were used to identify the main themes that emerged from the data collection results, which were then interpreted to provide a deeper understanding of the effectiveness of Islamic educational leadership in the digital era. The results of the research show that the traditional approach to leadership in Islamic education at MAN 2 Banyuwangi tends to face challenges in integrating technology and modern educational innovation, the form of which is adopting digital technology and the needs of millennial era society and the controversy surrounding the effectiveness of leadership in Islamic education is not only limited to the debate between traditional and modern, but also includes differences of opinion in interpreting Islamic values ​​in the current context, one of the forms of which is continuing to develop Islamic values ​​education in the implementation of Ma'had Al Qosimy which adopts the Islamic boarding school education system such as sorogan, wetonan and bandongan in the study of poles.